2008
DOI: 10.1590/s0102-311x2008000200018
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da aplicação do protocolo de triagem pré-natal para toxoplasmose em Belo Horizonte, Minas Gerais, Brasil: estudo transversal em puérperas de duas maternidades

Abstract: A toxoplasmose, transmitida pelo Toxoplasma gondii, é uma das infecções parasitárias mais comuns em humanos, sendo amplamente distribuída em todo o mundo 1 . Quando a priminfecção ocorre durante a gestação, assume importância especial, pois 40% a 50% dos fetos podem ser infectados com possibilidade de desenvolver doença grave 2 . A idade gestacional da infecção materna tem papel determinante no risco da transmissão e no quadro clínico apresentado pela criança, pois quanto mais precoce, menor a possibilidade de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
2
11

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
5
15
2
11
Order By: Relevance
“…These observations agree with previous studies that indicate a percentage of IgG anti-T. gondii antibodies in the Brazilian population (20,(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…These observations agree with previous studies that indicate a percentage of IgG anti-T. gondii antibodies in the Brazilian population (20,(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 93%
“…6 In the present study more than 60% of the pregnant women tested positive for IgG anti-T. gondii antibodies, which is in agreement with other studies carried out in Brazil reporting seropositivity rates ranging from 22.8% to 71.5%. [7][8][9][10][11][12] Two recent studies performed in the northwest region of São Paulo State found rates similar to those reported in the current study. 5,13 Pregnant women at risk of congenital transmission of toxoplasmosis were younger than those without risk.…”
Section: Discussionsupporting
confidence: 91%
“…Some Brazilian states provide serological evaluation during prenatal care, but regardless, in most cases, these exams are performed too late to make a helpful diagnosis; furthermore, when the first exam is negative, there is no follow up in the subsequent months. Thus, there is no possibility of the early diagnosis of serological conversion and specific treatment during pregnancy 6 .…”
Section: Introductionmentioning
confidence: 99%